Penerapan Teknik Journaling untuk Meningkatkan Kinerja Konselor - Diova Laviria Alfirazi; Tanti Ardianti; Fijriani Fijriani (Teraputik: Jurnal Bimbingan dan Konseling)
The background of this research is based on the needs of students and the resolution of various issues faced by students, which serves as a significant motivation for a counselor to continually enhance their performance through personality, skills, creativity, knowledge, and competencies they possess. One of the areas that counselors should improve is their mastery of various techniques that can be applied in the counseling process to help address client problems. This type of research is qualitative in nature and employs a literature review approach, specifically, the Systematic Literature Review (SLR) method. The general objective of this research is to describe the performance of counselors. Based on the analysis, it was found that the journaling technique can be applied in addressing student issues.